Evaluation of microbiological and physical-chemistry of frozen hamburger patties expended in Maracaibo, Zulia State, Venezuela - Parra, Katynna; Piñero, María; Narvaez, Claudia; Uzcátegui, Soján; Arenas de Moreno, Lilia; Huerta Leidenz, Nelson (Revista Científica de la Facultad de Ciencias Veterinarias)
In order to evaluate the microbiological quality (Aerobic plate count=APC; total coliforms=CT; fecal coliforms=CF; Escherichia coli=Ec; Staphylococcus aureus= Sa and Salmonella spp) and physical- chemistry quality (moisture, total solids, protein, fat and ashes) of hamburgers sold in Maracaibo, Zulia State, Venezuela, 27 samples of three hamburger brands were collected at random (brands A and B: beef, C: chicken) commercialized in three retail markets over three weeks. In APC, brand A obtained more than 2,8 log10 ufc/g with respect to brand C (P < 0.05). For CT, brand B presented more NMP in relation to brands A and C in two of the retail markets sampled (P < 0.05), while the results obtained for CT in all three brands were varied. Salmonella spp was present in beef hamburgers of brand B. The APC count and E. coli exceeded the limits allowed in all brands. In the proximal analysis brand B had a lower quantity of protein (14,66% vs A=18.25% and C= 16.36%) due to a higher proportion of fat (17.95% vs A=13.94% and C=14.56%) which was constant in the three sampled retail markets. The high count in the microbiological indicators reflects a poor microbiological quality, suggesting the lack of good sanitary practices in manufacturing. The variability in the content of protein and fat in the three brands evidenced not only the difference in the commercial formula, but also that these types of hamburgers do not comply with Venezuelan bromatological standards.